Modeling the Anesthetic Effect of Ropivacaine after a Femoral Nerve Block in Orthopedic Patients: A Population Pharmacokinetic–Pharmacodynamic Analysis. (May 2015) - Gaudreault, François; Drolet, Pierre; Fallaha, Michel; Varin, France
Abstract : Background: Even though ropivacaine is frequently used during orthopedic surgery, the relationship between plasma concentrations and degree of sensory anesthesia after a peripheral nerve block is currently unknown. The aim of this study was to characterize this relation using population pharmacokinetic–pharmacodynamic modeling. Methods: Femoral nerve block was performed by the anterior approach using a single injection (20 ml) of 0.5% ropivacaine hydrochloride in 20 patients scheduled for total knee arthroplasty under spinal anesthesia. Sensory thresholds in response to a gradual increase in transcutaneous electrical stimulation (primary endpoints), loss and recovery of ice-cold sensation, as well as total ropivacaine plasma concentrations were determined up to 4 days after administration of the local anesthetic. Using NONMEM (ICON, USA), sensory block was modeled by assuming an equilibration delay ( k e0 ) between amount in the depot and effect-site compartments. Results: Mean effect-site amount producing 90% of the maximum possible effect ( AE 90 ) was estimated as 20.2 mg. At 2 × AE 90, the sigmoid E max model predicted a mean onset time of 23.4 min and mean duration of 22.9 h. Interindividual variability (IIV) for AE 50 was 49%. Typical k e0 half-life was 34.7 min (IIV = 52%) and steepness parameter 8.7 (IIV = 48%). None of the pharmacodynamic model parameters showed sex, age, or body weight dependency. Conclusions: A population pharmacokinetic/pharmacodynamic model was developed that quantitatively describes the sensory component of a femoral nerve block in orthopedic patients. Further clinical studies will be needed to validate the clinical relevance of this finding. Abstract : A population pharmacokinetic–pharmacodynamic model was developed that describes the relationship between sensory response and the amount of ropivacaine remaining at the site of injection after single-dose injection for femoral nerve block. Simulation using the model suggests that following a bolus dose of 100 mg, 0.2% ropivacaine hydrochloride should be infused at least at 3 ml/h to maintain a complete sensory block for 48 h.